PENGARUH BAHAN PELAPIS BENIH TERHADAP PERTUMBUHAN DAN HASIL TANAMAN JAGUNG (Zea mays L.) PADA CEKAMAN SALIN - Zunita, Vina Tasya; Supriyadi, Slamet; Rahman, Fahmi Arief; Yuhardi, Erick (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2024)
Maize is one of the most important food commodities after rice and is widely cultivated because it has a high protein value. The purpose of this study was to determine the effectiveness of the coating material on the growth and yield of maize under saline stress. This research was conducted in the Agroecotechnology greenhouse of the Faculty of Agriculture, University of Trunojoyo Madura from August 2022 to January 2023. This study used a factorial Completely Randomized Design (CRD) with 10 treatment combinations and 3 replications with a factor of one coating material (P) and a factor of two salinity (K). The coating material factor consisted of 5 treatments namely control (P0), bentonite (P1), biochar (P2), light coal (P3), and biochar compost (P4), the saline stress factor consisted of 2 treatments namely control (K0) and saline (K1). The results showed that the application of coating material to saline stress had a significant effect on all growth parameters. The interaction between treatments only had a significant effect on plant height at 1 MST, leaf area at 6 MST, and 100 seed weight. Treatment (P2K1) with biochar and saline showed the best results on all growth and yield parameters of maize. Saline stress reduced the percentage of growth and yield of maize by about 50%.